Hop to It! The Relationship Between Hop Tests and The Anterior Cruciate Ligament - Return to Sport Index After Anterior Cruciate Ligament Reconstruction in NCAA Division 1 Collegiate Athletes - Michael Zarro; Madelyn Dickman; Timothy Hulett; Robert Rowland; Derrick Larkins; Jeffrey Taylor; Christa Nelson (North American Sports Medicine Institute, 2023)
# Background Outcomes after anterior cruciate ligament reconstruction (ACLR) may not be optimal, with poor physical and psychological function potentially affecting return to sport (RTS) ability. Understanding the relationship between commonly used hop tests and the Anterior Cruciate Ligament -- Return to Sport Index (ACL-RSI) may improve rehabilitation strategies and optimize patient outcomes. # Hypothesis/Purpose The purpose of this study was to examine the relationship between ACL-RSI scores and limb symmetry index (LSI) for the single hop for distance (SHD), triple hop for distance (THD), crossover hop for distance (CHD), timed 6-meter hop (T6H), and single leg vertical hop (SLVH) in a cohort of National Collegiate Athletic Association (NCAA) Division 1 collegiate athletes after ACLR. The hypothesis was that SLVH LSI would be more highly correlated with ACL-RSI score than all horizontal hop tests. # Study design Cross-Sectional Study # Methods Twenty-one National Collegiate Athletic Association (NCAA) Division 1 collegiate athletes (7 males, 14 females) at 6.62 ± 1.69 months after ACLR were included in this retrospective study. Primary outcomes were ACL-RSI score and LSI for SHD, THD, CHD, T6H, and SLVH. The relationship between ACL-RSI scores and performance on hop tests (LSIs) was evaluated using correlation analysis and step-wise linear regression (p ≤ 0.05). # Results There were significant correlations found when comparing ACL-RSI and the LSI for SHD (r~s~ = 0.704, p \< 0.001), THD (r~s~ = 0.617, p = 0.003), CHD (r~s~ = 0.580, p = 0.006), and SLVH (r~s~ = 0.582, p = 0.006). The CHD explained 66% (R^2^ value of 0.660) of the variance in the ACL-RSI, while the other hop tests did not add to the predictive model. # Conclusions Physical function has the capacity to influence psychological status after ACLR. Clinicians should recognize that SLVH, SHD, THD, and CHD are correlated with ACL-RSI and improvements in physical function during rehabilitation may improve psychological status and optimize RTS after ACLR. # Level of evidence Level 3